INVESTIGACIÓN DE PRÁCTICA REFLEXIONADA EN LA EDUCACIÓN DE MAESTROS - Weiss, Michael Noah (Revista Internacional de Filosofía Aplicada HASER, 2021)
In this essay the approach of reflective practice research, as introduced by the philosopher Anders Lindseth, is outlined and its relevance for teacher education is discussed. For that purpose, central theoretical as well as methodological aspects of this research approach are presented and further investigated. By means of illustrative case studies, examples are given on how this approach can be of use for teacher students in order to develop research competence, on the one hand. On the other, this essay examines how a teacher can reflect his or her own practice, in terms of self-studies, in order to learn from experience and to develop towards so-called phronesis (practical wisdom or prudence).